PENGAJARAN AKUNTANSI PADA MURID SMA PELITA KASIH DENGAN METODE INTERAKTIF - Sutedja, Natasya Emillia; Sriwati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Teaching Assistance activities in the Education Unit are carried out at Pelita Kasih High School with a three-month teaching duration, from 1 September 2023 to 17 November 2023. This implementation targets 12th graders majoring in social science, with a total of 39 students. Teaching Assistance Activities in the Education Unit at Pelita Kasih High School discuss basic accounting material that will be used for them to enter the world of work or further education. This activity aims to increase Pelita Kasih High School student's knowledge of the material, support the educational process to be more collaborative, and give Pelita Kasih High School students more opportunities to engage with each other in a meaningful way by using interactive teaching methods, namely learning methods that encourage discussion between students which can provide benefits in increasing understanding of the material for Pelita Kasih High School students. This method can improve memory and effectiveness in remembering material that has been studied. The results of this activity went well. This can be seen from the questionnaire results regarding the benefits and understanding of the learning material given to Pelita Kasih High School students.